(3GdeYJeO aj CUhd Gdabgs - (3CHh GdbGSe Hf CMeO Hf Ydj Hf EHQGgje GdRjGfj , J (B1249 (3g`s
(3ChdgG (B:s
(3aCeG JQLjM GdYdg GdQGLY Edi aQhYgG s
(3BNQgG (B:s
(3HNdGa eG GOGg Edjg GLJgGOg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1732s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs